Role of endoscopic ultrasonography in the diagnosis of solid pseudo-papillary neoplasm: Egyptian multi-centric case series and systematic review - Hussein Okasha; Wael Abbas; Ahmed Altonbary; Hazem Hakim; Mahmoud Gamal Ameen; Mohamed El-Nady (SpringerOpen, 2022)
Abstract Solid pseudo-papillary neoplasm (SPPN) is a rare type of pancreatic tumor accounting for less than 2% of all pancreatic neoplasms. Accurate diagnosis of these tumors is very important for proper management. In this study, observations were documented from 18 consecutive cases diagnosed with SPPN using endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA). The data of 18 consecutive cases were prospectively collected and reviewed. The collected data included age, gender, symptoms, size and site of the lesion, and type of surgery performed, in addition to mortality and recurrence rates. The mean age of the included cases was 33 years, and most of them were females (94.44%). Abdominal pain was the common symptom, and the pancreatic body was the most affected site. EUS-FNA confirmed the diagnosis in all cases when compared to the surgical specimen obtained. Cases were treated either with pancreatico-duodenectomy or distal pancreatectomy. One case (1/18) had early postoperative mortality due to sepsis. The remaining cases developed no recurrence or metastasis during the follow-up period of 18 months. SPPN is not a common pancreatic tumor. Confirming the diagnosis plays a crucial role prior to surgery as it facilitates intraoperative planning; therefore, EUS-FNA is a golden standard method used to diagnose. Postoperative survival has improved if the tumor is completely removed. EUS-FNA technique is a minimally invasive technique that can provide high yielding in providing detailed diagnostic analysis of SPPN.